Outcomes Following Liver Transplantation for Patients with Alcohol- Versus Nonalcohol-Induced Liver Disease. (1st November 2000) - Abosh, Dory; Rosser, Barry; Kaita, Kelly; Bazylewski, Rose; Minuk, Gerald
Abstract : OBJECTIVE: To document and compare the outcomes of adult patients who received liver transplants for alcohol- and nonalcohol-induced liver diseases who attended a liver transplantation follow-up clinic in an urban, nontransplantation centre at a time when no formal alcohol abuse program for transplant candidates and/or recipients was offered. PATIENTS AND METHODS: The study population comprised 10 alcoholic patients and 48 nonalcoholic patients followed for an average of 41 months (range five to 79 months) and 46 months (range two to 116 months), respectively. Primary outcome variables included rates of recidivism, duration of abstinence after transplantation and compliance with post-transplant medical follow-up visits. Time to discharge after transplantation, episodes of graft rejection, liver and renal biochemical abnormalities, diabetes, hypertension, sepsis, strictures, complications unrelated to transplantation and changes in psychosocial status were secondary outcome variables. RESULTS: Significant differences were found with respect to a higher incidence of recidivism (50% for alcoholic patients compared with 2% for nonalcoholic patients, P<0.0001), a shorter period of abstinence after transplantation (14.7±17.2 months for alcoholic patients compared with 26.3±23.0 months for nonalcoholic patients, P<0.05) and more missed office visits (2.7±3.5 for alcoholic patients compared with 1.0±1.9 for nonalcoholic patients, P=0.05) in the alcoholic group. The alcoholic group also had a lower incidence of rejection episodes (10% for alcoholic patients compared with 44% for nonalcoholic patients, P<0.05) but higher rates of post-transplantation diabetes (40% for alcoholic patients compared with 2% for nonalcoholic patients, P<0.05), more nontransplantation-related complications (20% for alcoholic patients compared with 0% for nonalcoholic patients, P<0.05), and higher serum creatinine but lower bilirubin and cyclosporine A levels (P<0.05, respectively). Marital separations were also more common in the alcoholic group (20% for alcoholic patients compared with 0% for nonalcoholic patients, P<0.05). CONCLUSIONS: In the absence of formal alcohol abuse programs, the post-transplantation outcome in alcoholic patients generally does not compare well with that of patients who undergo transplantation for nonalcohol-related liver diseases.